Dynamic characteristics analysis of nonlinear suspension system of automobile with seven degree of freedom. (August 2019) - Jia, Hongyu; Yun, Chao; Wang, Ying
Abstract: The application of MATLAB/SIMULINK to establish the mechanical simulation model of seven-degree-of-freedom vehicle linear and non-linear suspension system. Realization of system response under simulated road excitation, the dynamic characteristics of the non-linear suspension are studied, the non-linear spring and damping are simulated, and the parameter ε is introduced to change the degree of nonlinearity. The root mean square values of acceleration and displacement of linear suspension, non-linear stiffness suspension and non-linear damping suspension are analyzed and compared under different pavement conditions. The results show that: The mean square root of the acceleration of the body mass center and the pitch angle of the non-linear suspension are reduced by 14.3% and 17.0% respectively compared with the linear acceleration of the body mass center and the pitch angle; The root mean square value of pitch acceleration of non-linear suspension damping is 31.2% less than that of linear acceleration, which improves ride comfort and safety to a certain extent.